Pendidikan Karakter Humanis-Religius Melalui Pendekatan Pengelolaan Kelas: Analisis Kualitatif Pedagodik Islam - Wildan Habibi; Ayu Agustina (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
This study analyzes the formation of students' humanist-religious character through a classroom management approach in Islamic Religious Education learning in high schools. This study is based on the assumption that character education cannot be reduced to the transmission of normative values, but must be understood as a pedagogical process that occurs through social, psychological, and spiritual relations in the classroom. The study uses a qualitative approach with a case study design, through in-depth interviews, learning observations, and documentation to capture the pedagogical practices of PAI teachers in a contextual and reflective manner. The research findings indicate that democratic, humanist, and freedom-based classroom management functions as a transformative medium in integrating humanitarian and religiosity values ​​simultaneously. PAI teachers act not only as conveyors of teaching materials, but also as moral-spiritual facilitators who build a participatory, empathetic, and reflective classroom climate. The novelty of this study lies in the conceptualization of classroom management as a values-based pedagogical instrument that bridges humanistic educational theory and Islamic character education, thereby broadening the understanding of the internalization of religious values ​​in the context of formal education. Theoretically, this research contributes to the development of character education studies by emphasizing that the effectiveness of Islamic Religious Education learning is largely determined by the design of pedagogical relationships, not solely by curriculum content. These findings recommend the need to integrate a humanist-religious classroom management approach into character education policies and practices in schools.